A comparison of the sensory and rheological properties of different cellulosic fibres for food. Issue 2 (24th January 2018) - Agarwal, Deepa; Hewson, Louise; Foster, Tim J.
Abstract : The impact of cellulosic dietary fibres on taste perception & application of softwood cellulosic fibres with a unique network structure for food. Abstract : The impact of different cellulosic microstructures formed by highly entangled fibre networks was studied for food applications as dietary fibre. This paper reports the impact of the microstructure on the rheological and sensory behaviour of the aqueous suspensions of particulate and fibrillated forms of softwood cellulosic fibres, and was compared with citrus fibres. An aqueous suspension of cellulosic fibres shows stable viscoelastic gel-like behaviour as a function of frequency. The particulate form of cellulosic fibres showed the lowest shear viscosity as compared with the entangled network system at comparable concentrations. To provide further insight into the relationship between the structure of cellulosic fibre and taste (salt) perception, an aqueous suspension with matched shear viscosities were studied. A hypothesis to explain why softwood cellulosic fibre (CTE) with an entangled network structure prolongs the taste perception is presented.